Field Research on Translation and Interpreting (John Benjamins Publishing Company, 2025)
This volume constitutes a significant step in establishing field research as a central methodological approach in translation and interpreting studies. Following an integrative approach, it addresses both translation and interpreting across professional, paraprofessional, and non-professional settings and discusses common aspects and challenges such as the researchers’ reflexivity, ethical considerations, and the role of materiality in fieldwork. The chapters in this volume focus on lived experiences in diverse, real-world contexts—including refugee centres, UN missions, NGOs, virtual environments, and the workplaces of specialised translators. Dieser Sammelband widmet sich als eine der ersten Publikationen umfassend der translationswissenschaftlichen Feldforschung und leistet damit einen wesentlichen Beitrag zur Konsolidierung und Etablierung dieses Forschungsbereichs. Die Beiträge bieten neue Einblicke in Übersetzungs- und Dolmetschpraktiken in unterschiedlichen sozialen Kontexten (u.a. in Flüchtlingszentren, NGOs, Übersetzungsagenturen, staatlichen und internationalen Institutionen) und diskutieren übergreifende methodologische Aspekte wie Reflexivität, Ethik oder Materialität in der Feldforschung.